Trang chủ
/
Toán
/
b. Tính giới hạn lim _(xarrow -infty )(sqrt (x^2+2x)cdot sqrt [3](x^3+3x^2-1)+x^2+2x)

Câu hỏi

b. Tính giới hạn lim _(xarrow -infty )(sqrt (x^2+2x)cdot sqrt [3](x^3+3x^2-1)+x^2+2x)
zoom-out-in

b. Tính giới hạn lim _(xarrow -infty )(sqrt (x^2+2x)cdot sqrt [3](x^3+3x^2-1)+x^2+2x)

expert verifiedXác minh chuyên gia

Giải pháp

4.4(257 phiếu bầu)
avatar
Trúc Linhngười xuất sắc · Hướng dẫn 8 năm

Trả lời

Ta có:<br />$\lim_{x \to -\infty} (\sqrt{x^2+2x}\sqrt[3]{x^3+3x^2-1} + x^2+2x)$<br /><br />Khi $x \to -\infty$, ta có $\sqrt{x^2+2x} = |x|\sqrt{1+\frac{2}{x}} = -x\sqrt{1+\frac{2}{x}}$ (vì $x<0$) và $\sqrt[3]{x^3+3x^2-1} = x\sqrt[3]{1+\frac{3}{x}-\frac{1}{x^3}}$.<br /><br />Do đó:<br />$\sqrt{x^2+2x}\sqrt[3]{x^3+3x^2-1} = -x\sqrt{1+\frac{2}{x}} \cdot x\sqrt[3]{1+\frac{3}{x}-\frac{1}{x^3}} = -x^2\sqrt{1+\frac{2}{x}}\sqrt[3]{1+\frac{3}{x}-\frac{1}{x^3}}$<br /><br />Khi $x \to -\infty$, $\sqrt{1+\frac{2}{x}} \to 1$ và $\sqrt[3]{1+\frac{3}{x}-\frac{1}{x^3}} \to 1$. Vậy:<br />$\sqrt{x^2+2x}\sqrt[3]{x^3+3x^2-1} \approx -x^2$<br /><br />Vì vậy:<br />$\lim_{x \to -\infty} (\sqrt{x^2+2x}\sqrt[3]{x^3+3x^2-1} + x^2+2x) = \lim_{x \to -\infty} (-x^2 + x^2 + 2x) = \lim_{x \to -\infty} 2x = -\infty$<br /><br />Đáp án đúng là $-\infty$.<br />